Synthesis Zeolite Y From Lapindo Mud With Variations Filling Autoclave And Ratio Molar Si/Al - Andarini, Novita; Maziyyah, Deys Sya’fatul; Haryati, Tanti; Sulistiyo, Yudi Aris; Suwardiyanto, S. (Universitas Jember, 2023)
Lapindo mud contains Silicate (SiO2), and Aluminum oxide (Al2O3) that can be utilized to synthesize zeolite Y. Zeolite Y was synthesized from Lapindo mud via the smelting and hydrothermal method, respectively. The thermal activation of Lapindo mud was achieved by leaching smelting at 550oC for 2 hours with NaOH to achieve thed desire adding SiO2, NaOH and aging for 48 hours. The effects of various parameters on the synthesis were investigated. The samples were characterized with X-ray Fluorescence (XRF), X-Ray Diffraction (XRD), Fourier Transformation Infrared Spectroscopy (FTIR) and Gas Sorption Analyzer (GSA). Zeolite Y with high crystallinity was synthesized under optimized conditions, such as filling autoclave 90% and a SiO2/ Al2O3 molar ratio of 15.